Slovenski prevod standardiziranega presejalnega testa za oceno disfagije - Groleger, Katja (Rehabilitacija (Ljubljana), 2013)
Introduction: Safe and appropriate nutrition is important for child development. Children with a developmental disability often present with eating and swallowing problems. Reliable clinical assessment is essential for the process of effective management and therapeutic treatment of children with disabilities. The study aimed to evaluate inter-raterreliability of the Slovenian translation of a standardized screening tool for assessment of eating and swallowing disorders the Dysphagia Disorder Survey (DDS). Methods: After parental consensus, the children were recorded during feeding or eating an usual meal. We assessed the recordings by using the second part of the DDS. In the analysis of inter-rater reliability, we compared the assessments from three speech therapists. Results: We evaluated 30 children with developmental neurological disorder, aged 2 to 17 years, who have had difficulty in feeding and swallowing. Statistical analysis of the assessment results revealed high inter-rater reliability of the total score (ICC = 0.964) and of the majority of individual items (ICCs between 0.629 and 0.932). Conclusions: The results of our study indicate that the Slovenian translation of the DDS is a reliable tool. We believe that the instrument is appropriate for assessment of eating disorders and swallowing in children with developmental neurological disorder in clinical practice.
Keywords: Adolescent; bolezni živčnega sistema; Cerebral Palsy; cerebralna paraliza; Child; Child, Preschool; Deglutition Disorders; Developmental Disabilities; developmental neurological disorder; eating and swallowing disorders; Eating Disorders; mladostnik; motnje hranjenja; motnje požiranja; Nervous System Diseases; otrok; predšolski otrok; razvojna nevrološka motnja; razvojne motnje; reliability; zanesljivost